Development of a Web-Based Interactive Multimedia Problem-Based Learning Approach on Algorithms and Programming Material - Ajeng Zanna Tirahna; R Mursid; Sriadhi Sriadhi (Randwick International of Education and Linguistics Science Journal, 2024)
This research and development aims to produce interactive multimedia based on problem-based learning (PBL) using the Web to improve student learning outcomes in algorithms and programming material that is feasible, practical, and effective. This type of development research uses the ADDIE model. This research was carried out at SMK Negeri 6 Mukomuko, the material on algorithms and programming in the informatics class X Phase E. The results of the research show: (1) Expert validation test on product material in the very feasible category, namely 88.14%. (2) The Instructional Design Expert validation test is in the very feasible category, namely 95.56%. (3) The Media Expert validation test is in the very feasible category, namely 91.46%. (4) Individual trials in the very good category, namely 87.55%. (5) The small group trial was in the very feasible category, namely 89.65%. And (6) field trials in the very feasible category, namely 89.15%. The practicality test was very practical, namely 96.67%, while the practicality test results for students were 95.59% in the very practical category. The results of the experiment using PBL-based interactive multimedia in the experimental class gave an average learning outcome of 84, while students who were taught without using PBL-based interactive multimedia got an average score of 60.9. Hypothesis testing uses an independent t-test with significant results. (2-tailed) of 0.00, where the result is <0.05, it is concluded that there is a significant difference between classes taught using PBL-based interactive multimedia and classes taught without using PBL-based interactive multimedia